Synthesis And Characterisation Of Electrospun Doped Tin(Iv) Oxide/ Polyaniline/Polyhydroxybutyrate Nanocomposite For Ethanol Gas Sensor - Inderan, Vicinisvarri (2019)
Semiconducting metal oxide/conducting polymer nanocomposite is a new class of material that combined the advantages of both metal oxide and polymer. Metal oxide based gas sensors tend to require high operating temperature, leading to high power consumption and short life time. In constrast, conductive polymers fit for low operating temperature usage, but they have slower response time. In order to overcome the limitations, a new electrospun nanocomposite based gas sensors were successfully developed by incorporating as-synthesised SnO2 nanorods into polyaniline (PANI) and polyhydroxybutyrate (P3HB). The as-synthesised materials were tested on ethanol (C2H5OH) gas using nitrogen (N2) as carrier gas. A facile hydrothermal method without using any organic template or surfactant was employed to synthesise undoped and doped SnO2 nanorods. The effects of various parameters namely pH, precursor concentration and duration of heat treatment were investigated. For the doped SnO2 nanorods, the effects of different types of metal dopant (Fe, Co, Ni and Pd) and the concentrations of each dopant (0.5, 1.0, 3.0 and 5.0 mol%) were also studied. The optimum condition for the synthesis of SnO2 nanorods powder was 180 ºC, pH 13, with a precursor concentration of 0.12 M and the duration of heat treatment of 24 hrs.